Transhumanizm i perspektywy jego oddziaływań na prawoznawstwo. Wybrane problemy - Sulikowski, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Currently, transhumanism is a growing and increasingly popular philosophical movement. Using the authority of the natural sciences strongly affects thinking about the future of humanity. Transhumanists not only formulate a vision of the human future, but also offer recommendations relating to the creation and application of law. This article is about the basics of transhumanism and its potential impacts on jurisprudence.
Keywords: transhumanizm; współczesna filozofia prawa; teoria prawa; orzecznictwo